Studying on Producing the Fluoresence Offset Printing Ink - Phung, Anh Tuan; Nguyen, Van Huy; Nguyen, Viet Cuong; Nguyen, Quang Hung (JST: Engineering And Technology For Sustainable Development, 2021)
The fluorescent offset printing inks are the popular materials used in security printing. The offset ink producing process includes two main steps such as mixing components and grinding ink. This paper presents the studied results regarding the determination of the optimized conditions of the fluorescent offset ink producing process. Three design factors as the varnish content, pigment content, and an enhanced degree of roller pressure are evaluated. The target of the regression function is the particle size of the fluorescent offset ink. The box-wilson steep ascent method and the first-order mathematical model were applied to design a factorial experiment. The optimal conditions obtained from the surface response are varnish content of 74 % by weight, pigment content of 16 % by weight, and pressure enhance of 20 bar. Additionally, the fluorescent offset ink samples prepared under the optimized conditions meet the standards of offset ink namely viscosity, tack value, particle size, and fluorescent properties.